The Positive Effect of Scramble Learning Model Assisted by Picture Cards on Students’ Learning Outcomes - Sukerti, Ni Ketut; Pudjawan, Ketut (Universitas Pendidikan Ganesha, 2020)
The problem of the low learning outcomes of Indonesian language is allegedly because teachers in the learning process tend to use less innovative methods. Therefore this research was conducted with the aim of finding out the significant effect between Indonesian Language learning outcomes of students who were taught with picture cards assisted by scramble learning model and students who were not taught with picture cards assisted by scramble learning model on grade IV students. This research used quasi experiment by using the Nonequivalent Control Group Design. The population in this research were all grade IV Elementary School students in Cluster X, Buleleng District in the academic year 2019/2020, consisted of 126 students.Sampling technique used in this research was cluster random sampling technique by using lottery. The sample used in this research was all fourth grade students of SDN 3 Kaliuntu consisted of 20 students as the experimental group and students on fourth grade students of SDN 1 Kaliuntu as many as 27 studnets as the control group. Indonesian learning outcomes data were collected by using the test method and instrument in the form of a multiple choice objective test (multiple choice test) then analyzed by using t-test. The results of the calculation of the analysis obtained t-count = 7.78 compared with t-table at a significance level of 5% (db) = 20 + 27-2 = 45 so that the price of t-table = 2.02 was obtained. The results showed the average value of the experimental group was higher than the average value of the control group (16.4> 10).Based on the results of the analysis of these data it can be concluded that there was a significant effect of the picture cards scramble learning model on the learning outcomes of Indonesian language on grade four students of Elementary School, Cluster X in Buleleng District in the academic year 2019/2020.